Effect of Ramadan fasting on body water status markers after a rugby sevens match - Trabelsi, K.; Rebai, H.; Abed, K. E.; Stannard, S. R.; Masmoudi, L.; Sahnoun, Z.; Hakim, A.; Fellman, N.; Tabka, Z. (Asian Journal of Sports Medicine, 2011)
Purpose: To evaluate the effect of Ramadan fasting on body water status markers of rugby players at basal condition and following a simulation of rugby sevens match. Methods: Twelve recreational rugby sevens players played three matches: one day before Ramadan (before Ramadan), at the end of the first week of Ramadan (Beg-R) and at the end of Ramadan (End-R). Before and immediately after each match, body weight was determined and blood samples were taken for the measurement of body water status markers. Total body water was measured with an impedancemeter only before matches. Results: At rest, an increase in hematocrit (+4.4%, P=0.03), hemoglobin (+3.4%, P=0.01) and plasma osmolarity (+2.8%, p<0.001) was noticed at End-R compared to before Ramadan. Total body water measured before Ramadan did not differ significantly from that of Ramadan. After the match, values of hematocrit and plasma osmolarity increased significantly at End-R (+1.4%, P=0.02; +3.1%, P<0.001 respectively) compared to before Ramadan. Although, hemoglobin measured after matches occurring during Ramadan did not differ from those of before Ramadan. In response to matches, the change of percentage of body water status markers did not differ during each period of the investigation. Conclusions: The present results show that Ramadan fasting induces dehydration at basal conditions. Also, rugby sevens match played during Ramadan did not exacerbate the magnitude of responses to matches of blood and body water status markers.